From Dusk to Dawn: Analysis of Anti-Money Laundering and Financing of Terrorism (AML/CFT) through Policymaking Stages in Kazakhstan and Kyrgyz Republic - Daniyar Sarbagishev; Mergen Dyussenov (Journal of Contemporary Governance and Public Policy, 2020)
The article looks into Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) policy issues through all stages of a policymaking process, across two Central Asian nations, Kazakhstan and Kyrgyz Republic . It does so through the prism of the role of key actors at each stage of policymaking. Among the key findings of this paper is that the implementation of anti-laundering policy in Kyrgyzstan has constantly been confronted with opposition from a range of key actors, specifically fractions within the parliament, as well as business communities and NGOs, while Kazakhstan faced policy implementation hurdles in a much less degree since both chambers of the national parliament did not express open resistance to the adoption of new amendments to the basic Law. Despite the higher resistance to AML/CFT policy implementation in the Kyrgyz parliament vis-à-vis its Kazakh counterpart, Kyrgyz Republic succeeded in passing the new Law due to a change in political power in 2017. Although both Kazakhstan and Kyrgyz Republic appear to move in the same policy direction overall while taking adequate measures to improve their AML/CFT policy systems in accordance with international standards, the specific stages of policymaking reveal interesting discrepancies, especially at the policy formulation and decision-making stages. This research appears to be the first and somewhat unique scholarly attempt to analyze a policy issue through a comprehensive policymaking cycle, i.e. all the way from agenda-setting to policy evaluation. More importantly, it looks into Central Asian context, the region that remains largely understudied.